Bureaucratizing Fatwā in Indonesia: The Council of Indonesian Ulama and Its Quasi-Legislative Power - Alfitri Alfitri (Universitas Islam Negeri Mataram, 2020)
The state has given de-jure recognition of the Council of Indonesian Ulama's (MUI) authority in establishing sharīʿa principles for the running of Islamic financial service in Indonesia. Given this extensive design, does MUI then expand this authority into other Islamic law fields, and if so, why and how MUI does that. This paper aims to examine MUI's policy to bureaucratize fatwā by making its Fatwa Commission the single institution, administratively and substantively, for fatwā production in Indonesia. It considers this issue in light of secondary data gathered through the documentation of Ijtima Ulama resolutions. It examines their inclusion or exclusion into the MUI's official fatwā compilation employing both normative-doctrinal and socio-legal analysis. As its formal role in the state system for the administration of Islamic legal traditions has been acknowledged, MUI continues expanding its authority by enabling its Fatwa Commission like a legislature, which will further review the Ijtima Ulama resolutions before promulgating them as a fatwā. Therefore, some of the resolutions that do not pass the review cannot/are not promulgated as a fatwā. MUI adopts this measure to increase the efficacy of its fatāwā by polishing the collective ijtihād resolutions of Ijtima Ulama which are assumed to represent all ulama in Indonesia.